Cord Blood Antibody Seroprevalance Against Diphtheria, Pertussis, Measles, Mumps and Rubella among Term Healthy Indian Newborns. (4th October 2017) - James, Deepak; Lavanya, Jula; Verma, Sanjay; Rawat, Amit; S, Venkataseshan; Aggarwal, Neelam
Abstract: Background: The resurgence of vaccine preventable diseases in young infants is a matter of concern worldwide. The aim of our study was to determine the seroprevalance of protective antibodies against diphtheria, pertussis, measles, mumps and rubella antigens in cord blood among term Indian newborns, at birth. Methods: Apparently healthy term newborns, delivered at a tertiary care hospital in Northern India, over two year period (Apr 15-March 17) were enrolled after taking informed written consent from their parents; and their cord blood sample was collected. Ethical clearance was obtained from Institute Ethics committee, before enrolling subjects. Cord blood samples were tested for antibodies using commercial ELISA kits IMMUNOLAB IgG. Results: A total of 160 newborns (M:F = 86:74) were enrolled. In our study, antibodies (IgG) against diphtheria toxin (DT) were > 0.1 IU/mL in 44.4% (71/160), 0.01 to 0.1 IU/mL in 53.1% (85/160) and < 0.01 IU/mL in 2.5% (4/160). None of their mothers received Tdap vaccine in past. Antibodies (IgG) against pertussis toxin (PT) > 40 U/mL were seen in 41.2% (66/160). Out of these 66 children, 23 had titres > 100 U/mL. Total of 58.8% (94/160) children had antibodies < 40 U/mL. Out of these 94 children, 48 had titers < 20 U/mL. Antibodies (IgG) against measles antigen were > 12 IU/mL in 88.8% (142/160). A total of 11.2 (18/160) had titers below 12 IU/mL. Out of these 18 children, 5 had titers < 6 IU/mL. Antibodies (IgG) against mumps antigen were > 12 IU/mL in 83.1% (133/160). A total of 16.9% (27/160) had titers below 12 IU/mL. Out of these 27 children, 12 had titers < 6 IU/mL. Antibodies (IgG) against rubella antigen were > 12 IU/mL in 83.7% (134/160). A total of 16.3% (26/160) had titers below 12 IU/mL. Out of these 26 children, 22 had titers < 6 IU/mL. Conclusion: Only 44.4% of studied newborns were fully protected (> 0.1 IU/mL) against diphtheria, because of maternal antibodies. As correlates of protection for pertussis are not yet defined; those having anti-PT titers >100 IU/mL i.e., 14.3% (23/160) were most protected; while those having titers < 20 U/mL i.e., 30% (48/160) were least protected. Out of studied newborns, fully protected (>12 IU/mL) against measles, mumps and rubella were 88.8%, 83.1% and 83.7% respectively. Acknowledgement. PGI Intramural research grant Disclosures: All authors: No reported disclosures.